Single-Bilayer Graphene Test Structures for Kelvin Probe Microscopy - Sergey P. Lebedev; Ilya A. Eliseyev; Mikhail S. Dunaevskiy; Ekaterina V. Gushchina; Alexander A. Lebedev (C, 2023)
A new technique for determining the point spread function, which is required for measuring the surface potential using Kelvin probe microscopy (KPM), is presented. The method involves using a silicon carbide substrate coated with single-layer and bilayer graphene as a test structure and obtaining KPM potential profiles in different directions on the surface. This makes it possible to determine the KPM point spread function, which can be used to perform deconvolution and accurately recover the surface potential.